Myofascial Pain in Patients Waitlisted for Total Knee Arthroplasty - Richard Henry; Catherine M Cahill; Gavin Wood; Jennifer Hroch; Rosemary Wilson; Tracy Cupido; Elizabeth VanDenKerkhof (Pain Research and Management)
BACKGROUND: Knee pain is one of the major sources of pain and disability in developed countries, particularly in aging populations, and is the primary indication for total knee arthroplasty (TKA) in patients with osteoarthritis (OA).